A fluorine-free, soft, non-yellowing waterproofing agent and its preparation method and application
By using AG doped nano -titanium dioxide/silicon dioxide soluble complexes and polyphyl hydrogen bephyfu ether glycol and polyal glycol to prepare fluoride soft, soft -free waterproof waterproofing agents, solve the problem of yellow transformation of waterproof textiles, and achieve high -performance waterproof , Soft and durable.
Patent Information
- Application Number
- CN202410857757.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-28
AI Technical Summary
Existing waterproof textiles are prone to yellowing after being waterproofed by waterproofing agents, which affects their appearance and performance.
AG doped nano -doped titanium dioxide/silicon dioxide soluble complexes and polythexide furavill ether glycol and polyal glycol to prepare fluoride, soft yellow -free waterproofing agent, and form a low surface tension state by cross -linking reactions to prevent water droplets wet and wet and penetration.
The excellent waterproof performance, good softness, good yellow degeneration performance, and strong durability of textiles are realized.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproofing agents, and in particular to a fluorine-free, soft, non-yellowing waterproofing agent and a preparation method and application thereof. Background Art
[0002] In order to give textiles waterproof and moisture-proof functions, waterproofing agents are often used to waterproof textiles. Waterproofing agents are currently involved in many application fields of textiles, such as jackets, tents, luggage fabrics and umbrellas. Waterproofing agents can be divided into two categories: fluorine-containing and fluorine-free. Among them, fluorocarbon finishing agents can give textiles excellent waterproof and oil-proof properties, but due to the harmfulness of PFOA and PFOS, their use has gradually been banned or restricted. Compared with perfluorinated compounds, fluorine-free waterproofing agents are more environmentally friendly and safer, and they will gradually become the mainstream in the field of waterproof finishing.
[0003] Currently, common fluorine-free waterproofing agents include polyurethane waterproofing agents, silicone waterproofing agents, and acrylate waterproofing agents. Among them, polyurethane waterproofing agents are mainly made of polyurethane resins, which have good waterproof properties and good air permeability, as well as good elasticity and ductility, and are suitable for waterproofing of various textiles. The domestic patent with application number 201911401319.4 discloses a soft fluorine-free waterproofing agent and its preparation method. The fluorine-free waterproofing agent provided by the present invention is formed by block copolymerization of dimer acid, polyol, aliphatic isocyanate and cross-linking monomer to form a nano fluorine-free waterproofing agent emulsion; at the same time, a water-dispersible isocyanate emulsion synthesized with hexamethylene diisocyanate trimer as raw material, N-methyldiethanolamine as water-soluble monomer and butanone oxime as end-capping agent is synthesized as a cross-linking agent; and the emulsion is compounded and modified with the aforementioned nano fluorine-free waterproofing agent emulsion, under certain temperature conditions, the end-capping isocyanate is unblocked, reacts with the cross-linking monomer in the waterproofing agent, and after cross-linking and film formation, a low surface tension state is formed, which effectively prevents the wetting and penetration of water droplets, and finally forms a new fluorine-free waterproof finishing agent. The fluorine-free waterproofing agent can improve the washability and waterproofness of textiles, and has a soft hand feel and good elasticity.
[0004] However, with the improvement of living standards, people have higher and higher requirements for the comfort, appearance and durability of waterproof textiles. Some textile fabrics will turn yellow after being waterproofed with waterproof agents, which will easily affect the appearance of the textiles and may also deteriorate their performance. Therefore, the development of a polyurethane waterproofing agent with excellent waterproof performance and no yellowing is of great significance for the development of high-performance waterproof textiles. Summary of the invention
[0005] The invention provides a fluorine-free, soft, and non-yellowing waterproof agent, and a preparation method and application thereof. The waterproof agent does not contain fluorine, is safe and environmentally friendly, and is used to waterproof textiles, so that the textiles have excellent waterproof performance, good softness, excellent anti-yellowing performance, and strong durability.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0007] A fluorine-free, soft and non-yellowing waterproofing agent comprises the following raw materials in parts by weight: 23-32 parts of polytetramethylene ether diol, 15-23 parts of polypropylene glycol, 1.8-2.5 parts of 2,2-dihydroxymethyl propionic acid, 2-3.5 parts of alcohol chain extender, 22-35 parts of Ag-doped nano titanium dioxide / silicon dioxide sol composite, 20-25 parts of isophorone diisocyanate, 1.5-2.2 parts of catalyst, 25-35 parts of organic solvent, 1.5-3 parts of triethylamine and 160-230 parts of water.
[0008] Preferably, the molecular weight of the polytetramethylene glycol is 1000-2000; the molecular weight of the polypropylene glycol is 1200-1600.
[0009] Preferably, the preparation method of the Ag-doped nano-titanium dioxide / silicon dioxide sol composite comprises the following steps:
[0010] Add 0.5-1% of 3-glycidyloxypropyltrimethoxysilane by weight to the nano-silica sol, stir and mix, then add 2.5-5% of Ag-doped nano-titanium dioxide by weight of the nano-silica sol, and perform ultrasonic treatment for 60-90 minutes while stirring to obtain the product.
[0011] Preferably, the preparation method of Ag-doped nano-titanium dioxide comprises the following steps:
[0012] 1) Add butyl titanate to anhydrous ethanol A while stirring vigorously to obtain solution A; add deionized water, glacial acetic acid and silver nitrate to anhydrous ethanol B, stir and mix to obtain solution B; the mass volume ratio of butyl titanate, anhydrous ethanol A, anhydrous ethanol B, deionized water, glacial acetic acid and silver nitrate is 20-25mL:40-50mL:40-50mL:3.5-4mL:13-16mL:0.25-0.5g;
[0013] 2) adding solution A to solution B while vigorously stirring solution B, and continuing stirring for 1-1.5 hours after the addition to obtain a sol, and then letting it stand to obtain a gel; placing the gel in an oven, drying it at 80-85° C., and then grinding it to obtain a grinding powder; calcining the grinding powder at 370-400° C. for 2-2.5 hours, and then naturally cooling it to room temperature to obtain the Ag-doped nano-titanium dioxide.
[0014] Preferably, the method for preparing the nano-silica sol comprises the following steps:
[0015] 30-32 parts by weight of anhydrous ethanol and 10-11 parts by weight of water are uniformly mixed, and then 0.4-0.45 parts by weight of concentrated ammonia water are dropped. After stirring and mixing, 3.2-3.7 parts by weight of tetraethoxysilane are slowly dropped into the mixed solution. The addition is completed over 30-50 minutes, and then stirring is continued at a speed of 500-800 r / min for 2-3 hours to obtain the nano silica sol.
[0016] Preferably, when the ultrasonic treatment is performed while stirring, the stirring speed is 300-600r / min, and the ultrasonic power is 500-900W.
[0017] Preferably, the alcohol chain extender is at least one of 1,4-butanediol and neopentyl glycol.
[0018] Preferably, the catalyst is an organic titanium catalyst, which may be specifically tetrabutyl titanate; and the organic solvent is acetone.
[0019] As a general inventive concept, the present invention also provides a method for preparing a fluorine-free, soft, non-yellowing waterproofing agent, comprising the following steps:
[0020] S1: Add polytetramethylene glycol, polypropylene glycol, and isophorone diisocyanate to the reactor, stir and heat to 85-90°C, then add the catalyst, react for 1-2h, cool to 60-65°C, add the organic solvent, stir and mix, then add 2,2-dimethylol propionic acid and alcohol chain extender, continue to stir and react for 2.5-4h, then cool to below 50°C, add triethylamine, continue to stir for 25-40min, slowly add water for emulsification, and obtain a polyurethane emulsion;
[0021] S2: Adding Ag-doped nano-titanium dioxide / silicon dioxide sol composite to the polyurethane emulsion, stirring and mixing for 60-80 minutes, and then performing reduced pressure distillation to remove the organic solvent, thereby obtaining the fluorine-free, soft, non-yellowing waterproofing agent.
[0022] As a general inventive concept, the present invention also provides a fluorine-free, soft, non-yellowing waterproof agent or the use of the fluorine-free, soft, non-yellowing waterproof agent prepared by the above preparation method in waterproof finishing of textiles.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. When preparing a fluorine-free, soft, and non-yellowing waterproofing agent, the present invention adds an Ag-doped nano-titanium dioxide / silicon dioxide sol composite. The nano-titanium dioxide and Ag in the Ag-doped nano-titanium dioxide cooperate with each other to effectively prevent the polyurethane waterproofing agent from yellowing. In addition, in the Ag-doped nano-titanium dioxide / silicon dioxide sol composite of the present invention, the Ag-doped nano-titanium dioxide has high dispersibility. When the waterproofing agent is subsequently prepared, it can also be highly dispersed in the waterproofing agent, thereby effectively exerting its yellowing resistance.
[0025] In addition, when Ag-doped nano-titanium dioxide / silicon dioxide sol composite is used to prepare waterproofing agent, Ag-doped nano-titanium dioxide and nano-silicon dioxide are combined to significantly improve the roughness of the textile surface, thereby significantly improving the waterproofing performance. The silica sol prepared by the method of the present invention has good film-forming performance, and when added to polyurethane, it can also improve the overall stability of polyurethane, thereby improving the waterproofing performance of the waterproofing agent, and also enhancing the yellowing resistance of the waterproofing agent.
[0026] 2. The present invention uses polytetrahydrofuran ether diol and polypropylene glycol as main polyols to react with isophorone diisocyanate to prepare a waterproofing agent, wherein the structure of polytetrahydrofuran ether diol contains a large amount of ether bonds -O- and neatly arranged methylene groups -CH2-, and the structure makes the polyurethane prepared by it have higher water resistance, and polytetrahydrofuran ether diol can also improve the crystallinity of polyurethane molecular chains, so that the overall strength of polyurethane is improved, and then has excellent washing resistance, and can maintain structural stability for a long time during use, and has good durability. In addition, polypropylene glycol is used as a raw material for polyurethane soft segments, and its molecular chain is soft, contains ether bonds and is rotatable, which can effectively improve the softness of polyurethane. Polytetrahydrofuran ether diol and polypropylene glycol cooperate with each other, effectively ensuring the waterproof performance of the obtained waterproofing agent, and making it have higher strength, and can also make the finished textiles have excellent softness.
[0027] 3. The waterproofing agent in the present invention does not contain fluorine, is safe and environmentally friendly, and the use of the waterproofing agent to waterproof textiles can make the textiles have excellent waterproof performance, good softness, excellent anti-yellowing performance, and good durability. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Preparation Example 1: Preparation of Ag-doped nano-titanium dioxide / silicon dioxide sol composite
[0030] The preparation method of Ag-doped nano-titanium dioxide / silicon dioxide sol composite comprises the following steps:
[0031] 1% by weight of 3-glycidyloxypropyltrimethoxysilane was added to the nano-silica sol, and after stirring and mixing, 4% by weight of Ag-doped nano-titanium dioxide was added to the nano-silica sol, and ultrasonic treatment was performed for 90 minutes while stirring. The stirring speed was 400 r / min and the ultrasonic power was 900 W, so as to obtain an Ag-doped nano-titanium dioxide / silica sol composite.
[0032] The preparation method of Ag-doped nano-titanium dioxide comprises the following steps:
[0033] 1) Add butyl titanate to anhydrous ethanol A while stirring vigorously to obtain solution A; add deionized water, glacial acetic acid and silver nitrate to anhydrous ethanol B, stir and mix to obtain solution B; the mass volume ratio of butyl titanate, anhydrous ethanol A, anhydrous ethanol B, deionized water, glacial acetic acid and silver nitrate is 25mL:40mL:45mL:3.5mL:13mL:0.35g;
[0034] 2) Add solution A to solution B while vigorously stirring solution B. Continue stirring for 1.5 hours after the addition to obtain a sol, and then let it stand for 2 days to obtain a gel; place the gel in an oven, dry it at 85°C, and then grind it to obtain a grinding powder; calcine the grinding powder at 400°C for 2.5 hours, and then naturally cool it to room temperature to obtain Ag-doped nano-titanium dioxide.
[0035] The preparation method of nano silica sol comprises the following steps:
[0036] 30 parts by weight of anhydrous ethanol and 10 parts by weight of water were mixed evenly, and then 0.45 parts by weight of concentrated aqueous ammonia was dropped into the mixture. After stirring and mixing, 3.5 parts by weight of tetraethoxysilane was slowly dropped into the mixture. The addition was completed within 40 minutes, and then stirring was continued at a speed of 800 r / min for 3 hours to obtain a nano-silica sol.
[0037] Preparation Example 2: Preparation of Ag-doped nano-titanium dioxide / silicon dioxide sol composite
[0038] The preparation method of Ag-doped nano-titanium dioxide / silicon dioxide sol composite comprises the following steps:
[0039] 0.5% by weight of 3-glycidyloxypropyltrimethoxysilane was added to the nano-silica sol, and after stirring and mixing, 2.5% by weight of Ag-doped nano-titanium dioxide was added to the nano-silica sol, and ultrasonic treatment was performed for 70 minutes while stirring. The stirring speed was 600 r / min and the ultrasonic power was 500 W, so as to obtain an Ag-doped nano-titanium dioxide / silica sol composite.
[0040] The preparation method of Ag-doped nano-titanium dioxide comprises the following steps:
[0041] 1) Add butyl titanate to anhydrous ethanol A while stirring vigorously to obtain solution A; add deionized water, glacial acetic acid and silver nitrate to anhydrous ethanol B, stir and mix to obtain solution B; the mass volume ratio of butyl titanate, anhydrous ethanol A, anhydrous ethanol B, deionized water, glacial acetic acid and silver nitrate is 20mL:45mL:40mL:3.5mL:15mL:0.25g;
[0042] 2) Add solution A to solution B while vigorously stirring solution B, continue stirring for 1 hour after the addition to obtain a sol, and then let it stand for 3 days to obtain a gel; place the gel in an oven, dry it at 80°C, and then grind it to obtain a grinding powder; calcine the grinding powder at 370°C for 2 hours, and then naturally cool it to room temperature to obtain Ag-doped nano-titanium dioxide.
[0043] The preparation method of nano silica sol comprises the following steps:
[0044] 32 parts by weight of anhydrous ethanol and 11 parts by weight of water were mixed evenly, and then 0.4 parts by weight of concentrated aqueous ammonia was dropped into the mixture. After stirring and mixing, 3.2 parts by weight of tetraethoxysilane was slowly dropped into the mixture. The addition was completed over 50 minutes, and then stirring was continued at a speed of 500 r / min for 2 hours to obtain a nano-silica sol.
[0045] Preparation Example 3: Preparation of Ag-doped nano-titanium dioxide / silicon dioxide sol composite
[0046] The preparation method of Ag-doped nano-titanium dioxide / silicon dioxide sol composite comprises the following steps:
[0047] 0.7% by weight of 3-glycidyloxypropyltrimethoxysilane was added to the nano-silica sol, and after stirring and mixing, 5% by weight of Ag-doped nano-titanium dioxide was added to the nano-silica sol, and ultrasonic treatment was performed for 60 minutes while stirring. The stirring speed was 300 r / min and the ultrasonic power was 800 W, so as to obtain an Ag-doped nano-titanium dioxide / silica sol composite.
[0048] The preparation method of Ag-doped nano-titanium dioxide comprises the following steps:
[0049] 1) Add butyl titanate to anhydrous ethanol A while stirring vigorously to obtain solution A; add deionized water, glacial acetic acid and silver nitrate to anhydrous ethanol B, stir and mix to obtain solution B; the mass volume ratio of butyl titanate, anhydrous ethanol A, anhydrous ethanol B, deionized water, glacial acetic acid and silver nitrate is 22mL:50mL:50mL:4mL:16mL:0.5g;
[0050] 2) Add solution A to solution B while vigorously stirring solution B. Continue stirring for 1 hour after the addition to obtain a sol, and then let it stand for 2 days to obtain a gel; place the gel in an oven, dry it at 82°C, and then grind it to obtain a grinding powder; calcine the grinding powder at 390°C for 2 hours, and then naturally cool it to room temperature to obtain Ag-doped nano-titanium dioxide.
[0051] The preparation method of nano silica sol comprises the following steps:
[0052] 30 parts by weight of anhydrous ethanol and 11 parts by weight of water were mixed evenly, and then 0.42 parts by weight of concentrated aqueous ammonia was dropped into the mixture. After stirring and mixing, 3.7 parts by weight of tetraethoxysilane was slowly dropped into the mixture. The addition was completed within 30 minutes, and then stirring was continued at a speed of 600 r / min for 2.5 hours to obtain a nano-silica sol.
[0053] Embodiment 1:
[0054] A fluorine-free, soft, and non-yellowing waterproofing agent comprises the following raw materials in parts by weight: 27 parts of polytetramethylene glycol, 18 parts of polypropylene glycol, 1.8 parts of 2,2-dihydroxymethyl propionic acid, 2 parts of 1,4-butanediol, 35 parts of Ag-doped nano-titanium dioxide / silicon dioxide sol composite, 22 parts of isophorone diisocyanate, 2.2 parts of tetrabutyl titanate, 30 parts of acetone, 2 parts of triethylamine, and 200 parts of water.
[0055] The molecular weight of the polytetramethylene glycol is 2000; the molecular weight of the polypropylene glycol is 1200. The Ag-doped nano-titanium dioxide / silicon dioxide sol composite is prepared by the method in Preparation Example 1.
[0056] The preparation method of the fluorine-free, soft and non-yellowing waterproof agent comprises the following steps:
[0057] S1: Add polytetrahydrofuran ether diol, polypropylene glycol, isophorone diisocyanate to a reactor (equipped with a stirrer, a thermometer, and a condensing reflux device), stir and heat to 90°C, then add tetrabutyl titanate, react for 2 hours, cool to 60°C, add acetone, stir and mix, then add 2,2-dihydroxymethyl propionic acid and 1,4-butanediol, continue to stir and react for 4 hours, then cool to below 50°C, add triethylamine, continue to stir for 25 minutes, slowly add water for emulsification, and obtain a polyurethane emulsion;
[0058] S2: Adding Ag-doped nano-titanium dioxide / silicon dioxide sol composite to the polyurethane emulsion, stirring and mixing for 80 minutes, and then performing reduced pressure distillation to remove organic solvents (acetone, ethanol), to obtain a fluorine-free, soft, non-yellowing waterproofing agent.
[0059] Embodiment 2:
[0060] A fluorine-free, soft, and non-yellowing waterproofing agent comprises the following raw materials in parts by weight: 32 parts of polytetramethylene glycol, 20 parts of polypropylene glycol, 2 parts of 2,2-dihydroxymethyl propionic acid, 3.5 parts of neopentyl glycol, 28 parts of Ag-doped nano-titanium dioxide / silicon dioxide sol composite, 20 parts of isophorone diisocyanate, 1.8 parts of tetrabutyl titanate, 25 parts of acetone, 1.5 parts of triethylamine, and 210 parts of water.
[0061] The molecular weight of the polytetramethylene glycol is 2000; the molecular weight of the polypropylene glycol is 1600. The Ag-doped nano-titanium dioxide / silicon dioxide sol composite is prepared by the method in Preparation Example 3.
[0062] The preparation method of the fluorine-free, soft and non-yellowing waterproof agent comprises the following steps:
[0063] S1: Add polytetrahydrofuran ether diol, polypropylene glycol, isophorone diisocyanate to a reactor (equipped with a stirrer, a thermometer, and a condensing reflux device), stir and heat to 85°C, then add tetrabutyl titanate, react for 2 hours, cool to 65°C, add acetone, stir and mix, then add 2,2-dimethylol propionic acid and neopentyl glycol, continue to stir and react for 2.5 hours, then cool to below 50°C, add triethylamine, continue to stir for 40 minutes, slowly add water for emulsification, and obtain a polyurethane emulsion;
[0064] S2: Adding Ag-doped nano-titanium dioxide / silicon dioxide sol composite to the polyurethane emulsion, stirring and mixing for 70 minutes, and then performing reduced pressure distillation to remove organic solvents (acetone, ethanol), to obtain a fluorine-free, soft, non-yellowing waterproofing agent.
[0065] Embodiment 3:
[0066] A fluorine-free, soft, and non-yellowing waterproofing agent comprises the following raw materials in parts by weight: 23 parts of polytetramethylene glycol, 15 parts of polypropylene glycol, 2.2 parts of 2,2-dihydroxymethyl propionic acid, 3 parts of 1,4-butanediol, 35 parts of Ag-doped nano-titanium dioxide / silicon dioxide sol composite, 20 parts of isophorone diisocyanate, 2.2 parts of tetrabutyl titanate, 30 parts of acetone, 1.5 parts of triethylamine, and 160 parts of water.
[0067] The molecular weight of the polytetramethylene glycol is 1000; the molecular weight of the polypropylene glycol is 1500. The Ag-doped nano-titanium dioxide / silicon dioxide sol composite is prepared by the method in Preparation Example 2.
[0068] The preparation method of the fluorine-free, soft and non-yellowing waterproof agent comprises the following steps:
[0069] S1: Add polytetrahydrofuran ether diol, polypropylene glycol, isophorone diisocyanate to a reactor (equipped with a stirrer, a thermometer, and a condensing reflux device), stir and heat to 88°C, then add tetrabutyl titanate, react for 1 hour, cool to 60°C, add acetone, stir and mix, then add 2,2-dihydroxymethyl propionic acid and 1,4-butanediol, continue to stir and react for 3.5 hours, then cool to below 50°C, add triethylamine, continue to stir for 30 minutes, slowly add water for emulsification, and obtain a polyurethane emulsion;
[0070] S2: Add Ag-doped nano-titanium dioxide / silicon dioxide sol composite to the polyurethane emulsion, stir and mix for 60 minutes, and then perform reduced pressure distillation to remove organic solvents (acetone, ethanol) to obtain a fluorine-free, soft, non-yellowing waterproofing agent.
[0071] Embodiment 4:
[0072] A fluorine-free, soft, and non-yellowing waterproofing agent comprises the following raw materials in parts by weight: 28 parts of polytetramethylene glycol, 23 parts of polypropylene glycol, 1.8 parts of 2,2-dihydroxymethyl propionic acid, 2 parts of 1,4-butanediol, 22 parts of Ag-doped nano-titanium dioxide / silicon dioxide sol composite, 22 parts of isophorone diisocyanate, 1.5 parts of tetrabutyl titanate, 25 parts of acetone, 2 parts of triethylamine, and 230 parts of water.
[0073] The molecular weight of the polytetramethylene glycol is 1000; the molecular weight of the polypropylene glycol is 1600. The Ag-doped nano-titanium dioxide / silicon dioxide sol composite is prepared by the method in Preparation Example 1.
[0074] The preparation method of the fluorine-free, soft, non-yellowing waterproof agent is the same as that of Example 1.
[0075] Embodiment 5:
[0076] A fluorine-free, soft, and non-yellowing waterproofing agent comprises the following raw materials in parts by weight: 32 parts of polytetramethylene glycol, 17 parts of polypropylene glycol, 2.5 parts of 2,2-dihydroxymethyl propionic acid, 3.5 parts of 1,4-butanediol, 28 parts of Ag-doped nano-titanium dioxide / silicon dioxide sol composite, 25 parts of isophorone diisocyanate, 2 parts of tetrabutyl titanate, 35 parts of acetone, 3 parts of triethylamine, and 200 parts of water.
[0077] The molecular weight of the polytetramethylene glycol is 2000; the molecular weight of the polypropylene glycol is 1200. The Ag-doped nano-titanium dioxide / silicon dioxide sol composite is prepared by the method in Preparation Example 2.
[0078] The preparation method of the fluorine-free, soft, non-yellowing waterproof agent is the same as that of Example 2.
[0079] Embodiment 6:
[0080] A fluorine-free, soft, and non-yellowing waterproofing agent comprises the following raw materials in parts by weight: 25 parts of polytetramethylene glycol, 22 parts of polypropylene glycol, 2.5 parts of 2,2-dihydroxymethyl propionic acid, 3 parts of neopentyl glycol, 25 parts of Ag-doped nano-titanium dioxide / silicon dioxide sol composite, 22 parts of isophorone diisocyanate, 1.5 parts of tetrabutyl titanate, 30 parts of acetone, 2 parts of triethylamine, and 180 parts of water.
[0081] The molecular weight of the polytetramethylene glycol is 1000; the molecular weight of the polypropylene glycol is 1500. The Ag-doped nano-titanium dioxide / silicon dioxide sol composite is prepared by the method in Preparation Example 1.
[0082] The preparation method of the fluorine-free, soft, non-yellowing waterproof agent is the same as that of Example 1.
[0083] Embodiment 7:
[0084] A fluorine-free, soft and non-yellowing waterproofing agent comprises the following raw materials in parts by weight: 29 parts of polytetramethylene glycol, 20 parts of polypropylene glycol, 1.8 parts of 2,2-dihydroxymethyl propionic acid, 3.5 parts of 1,4-butanediol, 32 parts of Ag-doped nano-titanium dioxide / silicon dioxide sol composite, 21 parts of isophorone diisocyanate, 1.8 parts of tetrabutyl titanate, 30 parts of acetone, 2.5 parts of triethylamine and 200 parts of water.
[0085] The molecular weight of the polytetramethylene glycol is 2000; the molecular weight of the polypropylene glycol is 1600. The Ag-doped nano-titanium dioxide / silicon dioxide sol composite is prepared by the method in Preparation Example 3.
[0086] The preparation method of the fluorine-free, soft, non-yellowing waterproof agent is the same as that of Example 2.
[0087] Comparative Example 1:
[0088] The difference from Example 1 is that the raw material Ag-doped nano-titanium dioxide / silicon dioxide sol is replaced by nano-titanium dioxide / silicon dioxide sol.
[0089] The preparation method of nano titanium dioxide / silicon dioxide sol composite comprises the following steps:
[0090] 1% by weight of 3-glycidyloxypropyltrimethoxysilane was added to the nano-silica sol, and after stirring and mixing, 4% by weight of nano-titanium dioxide was added to the nano-silica sol, and ultrasonic treatment was performed for 90 minutes while stirring. The stirring speed was 400 r / min and the ultrasonic power was 900 W, so as to obtain an Ag-doped nano-titanium dioxide / silica sol composite.
[0091] The preparation method of nano titanium dioxide comprises the following steps:
[0092] 1) Add butyl titanate to anhydrous ethanol A while stirring vigorously to obtain solution A; add deionized water and glacial acetic acid to anhydrous ethanol B, stir and mix to obtain solution B; the mass volume ratio of butyl titanate, anhydrous ethanol A, anhydrous ethanol B, deionized water, and glacial acetic acid is 25mL:40mL:45mL:3.5mL:13mL;
[0093] 2) Add solution A to solution B while vigorously stirring solution B. Continue stirring for 1.5 hours after the addition to obtain a sol, and then let it stand for 2 days to obtain a gel; place the gel in an oven, dry it at 85°C, and then grind it to obtain a grinding powder; calcine the grinding powder at 450°C for 2.5 hours, and then naturally cool it to room temperature to obtain nano titanium dioxide.
[0094] The remaining raw materials and preparation methods are basically the same as those in Example 1.
[0095] Comparative Example 2:
[0096] The difference from Example 1 is that the silica sol in the raw material Ag-doped nano-titanium dioxide / silicon dioxide sol is replaced by silica sol prepared by another method.
[0097] The preparation method of nano silica sol comprises the following steps:
[0098] 30 parts by weight of anhydrous ethanol and 7 parts by weight of water were mixed evenly, and then 0.7 parts by weight of concentrated aqueous ammonia was dropped into the mixture. After stirring and mixing, 3.5 parts by weight of tetraethoxysilane was slowly dropped into the mixture. The addition was completed within 40 minutes, and then stirring was continued at a speed of 800 r / min for 3 hours to obtain a nano-silica sol.
[0099] The remaining raw materials and preparation methods are basically the same as those in Example 1.
[0100] Comparative Example 3:
[0101] The difference from Example 1 is that the raw material Ag-doped nano-titanium dioxide / silicon dioxide sol is replaced by the Ag-doped nano-titanium dioxide in Preparation Example 1. The remaining raw materials and preparation method are basically the same as those in Example 1.
[0102] Comparative Example 4:
[0103] Different from Example 1, the waterproofing agent includes the following raw materials in parts by weight: 18 parts of polytetramethylene glycol, 27 parts of polypropylene glycol, 1.8 parts of 2,2-dihydroxymethylpropionic acid, 2 parts of 1,4-butanediol, 35 parts of Ag-doped nano-titanium dioxide / silica sol composite, 22 parts of isophorone diisocyanate, 2.2 parts of tetrabutyl titanate, 30 parts of acetone, 2 parts of triethylamine, and 200 parts of water.
[0104] The preparation method is basically the same as that in Example 1.
[0105] Performance Testing:
[0106] The waterproofing agent in the embodiment and the comparative example was prepared into a working solution with a mass fraction of 70 g / L, and natural cotton fabric (20 cm×20 cm) was waterproofed with the working solution, using a one-immersion and one-rolling process with a rolling rate of 90%, and then baked at 160°C for 2 minutes to obtain a waterproof finished cotton fabric.
[0107] The contact angle test was performed on the waterproof cotton fabrics obtained by the waterproof agents of the embodiment and the comparative example. The spray water test was performed according to AATCC22-2017 to evaluate the waterproof grade, and the waterproof grade of the waterproof cotton fabrics was evaluated again after washing 10 times; in addition, the yellowing resistance test was performed, and the evaluation criteria were: A: no yellowing at all; B: a little yellowing; C: obvious yellowing. The specific test results are shown in Table 1.
[0108] Table 1 Performance test results of waterproof finished cotton fabrics
[0109]
[0110] As shown in Table 1, the waterproofing agents in Example 1 of the present invention all have excellent waterproof performance, good durability, and good yellowing resistance. By comparing Example 1 with Comparative Example 1, it can be seen that if silver is not loaded on titanium dioxide, the yellowing resistance will be significantly reduced. By comparing Example 1 with Comparative Example 2, it can be seen that if the amount of each raw material added is changed when preparing silicon dioxide, the performance of the resulting silicon dioxide sol will also be changed, thereby adversely affecting the waterproofing performance of the waterproofing agent. By comparing Example 1 with Comparative Example 3, it can be seen that if Ag-doped nano titanium dioxide / silicon dioxide sol is replaced with Ag-doped nano titanium dioxide, yellowing resistance will also be affected, and the waterproofing performance of the waterproofing agent will be significantly reduced, and the durability will also deteriorate. By comparing Example 1 with Comparative Example 4, it can be seen that changing the amount of polytetrahydrofuran ether diol and polypropylene glycol added will deteriorate the waterproofing performance of the waterproofing agent.
[0111] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A fluorine-free, soft, non-yellowing waterproofing agent, characterized in that: The method comprises the following raw materials in parts by weight: 23-32 parts of polytetramethylene glycol, 15-23 parts of polypropylene glycol, 1.8-2.5 parts of 2,2-dimethylol propionic acid, 2-3.5 parts of alcohol chain extender, 22-35 parts of Ag-doped nano-titanium dioxide / silicon dioxide sol composite, 20-25 parts of isophorone diisocyanate, 1.5-2.2 parts of catalyst, 25-35 parts of organic solvent, 1.5-3 parts of triethylamine and 160-230 parts of water; The preparation method of the Ag-doped nano-titanium dioxide / silicon dioxide sol composite comprises the following steps: Add 0.5-1% of 3-glycidyloxypropyltrimethoxysilane by weight to the nano-silica sol, stir and mix, then add 2.5-5% of Ag-doped nano-titanium dioxide by weight of the nano-silica sol, and perform ultrasonic treatment for 60-90 minutes while stirring to obtain; The preparation method of the nano silica sol comprises the following steps: 30-32 parts by weight of anhydrous ethanol and 10-11 parts by weight of water are uniformly mixed, and then 0.4-0.45 parts by weight of concentrated ammonia water are dripped into the mixture, and after stirring and mixing, 3.2-3.7 parts by weight of tetraethoxysilane are slowly dripped into the mixture, and the dripping is completed over 30-50 minutes, and then stirring is continued at a speed of 500-800 r / min for 2-3 hours to obtain the nano silica sol; The preparation method of the fluorine-free, soft and non-yellowing waterproof agent comprises the following steps: S1: Add polytetramethylene glycol, polypropylene glycol, and isophorone diisocyanate to the reactor, stir and heat to 85-90°C, then add the catalyst, react for 1-2h, cool to 60-65°C, add the organic solvent, stir and mix, then add 2,2-dimethylol propionic acid and alcohol chain extender, continue to stir and react for 2.5-4h, then cool to below 50°C, add triethylamine, continue to stir for 25-40min, slowly add water for emulsification, and obtain a polyurethane emulsion; S2: Adding Ag-doped nano-titanium dioxide / silicon dioxide sol composite to the polyurethane emulsion, stirring and mixing for 60-80 minutes, and then performing reduced pressure distillation to remove the organic solvent, thereby obtaining the fluorine-free, soft, non-yellowing waterproofing agent.
2. The fluorine-free, soft, non-yellowing waterproofing agent according to claim 1, characterized in that: The molecular weight of the polytetramethylene glycol is 1000-2000; the molecular weight of the polypropylene glycol is 1200-1600.
3. The fluorine-free, soft, non-yellowing waterproofing agent according to claim 1, characterized in that: The preparation method of Ag-doped nano-titanium dioxide comprises the following steps: 1) Add butyl titanate to anhydrous ethanol A while stirring vigorously to obtain solution A; add deionized water, glacial acetic acid and silver nitrate to anhydrous ethanol B, stir and mix to obtain solution B; the mass volume ratio of butyl titanate, anhydrous ethanol A, anhydrous ethanol B, deionized water, glacial acetic acid and silver nitrate is 20-25mL:40-50mL:40-50mL:3.5-4mL:13-16mL:0.25-0.5g; 2) adding solution A to solution B while vigorously stirring solution B, and continuing stirring for 1-1.5 hours after the addition to obtain a sol, and then letting it stand to obtain a gel; placing the gel in an oven, drying it at 80-85° C., and then grinding it to obtain a grinding powder; calcining the grinding powder at 370-400° C. for 2-2.5 hours, and then naturally cooling it to room temperature to obtain the Ag-doped nano-titanium dioxide.
4. The fluorine-free, soft, non-yellowing waterproofing agent according to claim 1, characterized in that: When the ultrasonic treatment is performed while stirring, the stirring speed is 300-600r / min and the ultrasonic power is 500-900W.
5. The fluorine-free, soft, non-yellowing waterproofing agent according to claim 1, characterized in that: The alcohol chain extender is at least one of 1,4-butanediol and neopentyl glycol.
6. The fluorine-free, soft, non-yellowing waterproofing agent according to claim 1, characterized in that: The catalyst is an organic titanium catalyst; and the organic solvent is acetone.
7. Use of the fluorine-free, soft, non-yellowing waterproof agent as claimed in any one of claims 1 to 6 in waterproof finishing of textiles.
Citation Information
Patent Citations
Soft fluoride-free waterproof agent and preparation method thereof
CN111040105A
Preparation method of water-based polyurethane / nano-silicon dioxide composite emulsion
CN101845217A
Preparation method of fibroin-waterborne polyurethane nano composite waterproof leather finishing agent
CN106893467A